2021
DOI: 10.1021/acs.energyfuels.1c02140
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Nitrogen from Low-Cost Plant Feedstocks Used for Bioenergy: A Review of Availability and Process Order

Abstract: The cost of feedstock is often a major barrier to commercialization for lignocellulosic biofuels. Much of the research on biofuel and biobased chemical production has focused on the carbohydrate, lignin, and lipid components of biomass. There are numerous opportunities for the use of lower-cost feedstocks if more attention were devoted to the recovery and utilization of the protein and other N-containing components. This review compiles data from the last two decades on nonedible/ nonpalatable agricultural res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 302 publications
0
1
0
Order By: Relevance
“…Globally, rapeseed production is projected to be as high as 80.3 million tons in 2022, of which 30.7 and 37.9 million tons in the form of rapeseed oil and meal, respectively ( USDA, 2022 ). The extraction of rapeseed oil by pressing rapeseeds results in the production of raw rapeseed cake (RC), a by-product known for its rich content of protein, fiber, and minerals, which makes it a potential protein source for animal nutrition ( Bayat et al, 2021 ; Gao et al, 2022 ). Goiri et al (2021) showed that feeding diets containing RC to lactating dairy cows increased milk production.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, rapeseed production is projected to be as high as 80.3 million tons in 2022, of which 30.7 and 37.9 million tons in the form of rapeseed oil and meal, respectively ( USDA, 2022 ). The extraction of rapeseed oil by pressing rapeseeds results in the production of raw rapeseed cake (RC), a by-product known for its rich content of protein, fiber, and minerals, which makes it a potential protein source for animal nutrition ( Bayat et al, 2021 ; Gao et al, 2022 ). Goiri et al (2021) showed that feeding diets containing RC to lactating dairy cows increased milk production.…”
Section: Introductionmentioning
confidence: 99%